THE PRACTICE OF DIGITAL PAYMENT CULTURE ON JUMP START COFFEE MACHINES: A Consumer FGDnography of Bakrie University Students - Selvonia, Fadelia; Kania, Dessy (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
This article focuses on the behavior of student consumers about their experiences of purchases through e-wallets based on the stage of exposure, attention, and interpretation. The qualitative research was conducted using the FGDnography method, that is, a focus group discussion on the nature of the topic. The FGDnography was conducted for eight Bakrie University student participants, Jump Start Coffee consumers. The results show that the experience of Jump Start Coffee digital wallet payment methods at Bakrie University was practical and amusing because Jump Start Coffee vending machines provide a lot of convenience for consumers. Although there are some deficiencies, Jump Start Coffee is still considered a practical vending machine, including cashless payments that have fulfilled the lifestyle needs of millennial young people. To cite this article (7TH apa STYLE)::Selvonia, F. & Kania, D. (2021). The Practice of Digital Payment Culture on Jump Start Coffee Machines: A Consumer FGDnography of Bakrie University Students. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(2), 139-149. http://dx.doi.org/10.36782/jcs.v11i2.2023